Myanmar : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Myanmar during 1990-95. The rapid economic growth of 1992/93-1994/95, which averaged more than 7 percent per year, has allowed the economy to recoup much of what it lost in 1988/89 and 1991/92. However, on a per capita basis, neither GDP nor agricultural output has yet recovered to the levels reached in the mid-1980s. The strong GDP growth achieved in 1994/95 essentially reflected continued good performance of the agricultural sector and a further rapid expansion of the financial sector.